Effect of exercise on bone health in children and adolescents with cancer during and after oncological treatment: A systematic review and meta-analysis - Marmol-Perez, Andres; Ubago-Guisado, Esther; Rodriguez-Solana, Andrea; Gil-Cosano, Jose J.; Martinez-Vizcaino, Vicente; Cavero-Redondo, Ivan; Ruiz, Jonatan R.; Gracia-Marco, Luis (Frontiers in Physiology, 2023)
Background Although regular physical activity and exercise program might improve bone health caused by oncological treatment and the disease itself, it remains unknown the pooled effect of exercise interventions following frequency, intensity, time and type prescriptions. Objective This systematic review and meta-analysis aimed to synthesise evidence regarding the effectiveness of exercise interventions on bone health in children and adolescents with cancer during and after oncological treatment. Methods A systematic search was conducted in the MEDLINE (via PubMed), Web of Science and Scopus databases from November 2021 to January 2022. Randomized controlled trials (RCTs) and non-RCTs reporting pre-post changes of the effectiveness of exercise interventions on DXA-measured bone parameters in young population (1-19 years) during or after oncological treatment were included. Pooled effect sizes (ESs) and 95% confidence intervals (95%CIs) were calculated. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were followed. Results A total of eight trials with 341 participants were included. The meta-analyses did not reveal a statistically significant increase in whole body areal bone mineral density (ES=0.10; 95%CI: -0.14, 0.34), lumbar spine (ES=0.03; 95%CI: -0.21, 0.26) or femoral neck (ES=0.10; 95%CI: -0.37, 0.56). Similarly, during the oncological treatment phase the ES was 0.04 (95%CI: -0.17, 0.25) and after the ES was 0.07 (95%CI: -0.20, 0.33). Conclusion In comparison to standard care, exercise interventions were inappropriate and therefore, ineffective to illustrate any beneficial effect on bone health in children and adolescents with cancer during and after oncological treatment.